Inn i klasserommet - Harriet Bjerrum Nielsen (The Royal Danish Library, 2000)
Equality versus difference between girls and boys has been a returning issue in Scandinavian educational debates en this century. Until the turn of the century gendered differentiation was an explicit goal of education. While this lost favour in the period after the Second World War, when the political ideologiy of child centered development and learning gained dominance, many of the assumptions and practices constitutive of gendered difference remained remarkably intact.